2021
DOI: 10.1186/s12905-021-01419-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational program based on beliefs, subjective norms and perceived behavior control on doing pap-smear test in sample of Iranian women

Abstract: Objective Cervical cancer is considered treatable as long as it is detected early and managed effectively. Pap smear test is a screening tool that plays an important role in the early detection, prevention and can prevent any early cervical cell changes from becoming cancer. This study aims to survey the effect of educational programs based on beliefs, subjective norms, and perceived behavior control on doing the pap-smear test in a sample of Iranian women. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 36 publications
3
19
0
7
Order By: Relevance
“…The results showed that the mean scores of knowledge increased after the intervention, and a statistically significant difference was found between the two groups in terms of the knowledge before and after the intervention (p<0.001). This finding is similar to a body of research conducted by Pirzadeh and Amidi Mazaheri [ 19 ], Adamu et al [ 20 ], Gana et al [ 21 ], Karimy et al [ 22 ], Williams et al [ 23 ] and Jeihooni et al [ 24 ] and Jeihooni et al [ 25 ]. The findings reported by Pirzadeh and Amidi Mazaheri [ 19 ] also confirm that education increased women’s knowledge of the Pap smear test in the intervention group.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the mean scores of knowledge increased after the intervention, and a statistically significant difference was found between the two groups in terms of the knowledge before and after the intervention (p<0.001). This finding is similar to a body of research conducted by Pirzadeh and Amidi Mazaheri [ 19 ], Adamu et al [ 20 ], Gana et al [ 21 ], Karimy et al [ 22 ], Williams et al [ 23 ] and Jeihooni et al [ 24 ] and Jeihooni et al [ 25 ]. The findings reported by Pirzadeh and Amidi Mazaheri [ 19 ] also confirm that education increased women’s knowledge of the Pap smear test in the intervention group.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the finding in our study, in a study conducted with healthcare professionals in Turkey, the rate of knowing the cervical cancer screening program correctly was found to be higher in those who had previously received training on this subject [ 33 ]. In addition to these results, there are also experimental studies showing that the level of cervical cancer knowledge increases with the training given in the literature [ 34 , 35 ]. According to these findings, it is thought that it is vital that all healthcare professionals who are involved in providing services to the public in the early diagnosis and treatment of cancer are both informed about the subject during their vocational training and supported by in-service training.…”
Section: Discussionmentioning
confidence: 75%
“…The results of a study conducted by (Khani Jeihooni, Jormand, et al, 2021), using a quasi-experimental design method on 150 pregnant women in 2021 in Shiraz, Iran, showed a positive effect of the TPB model-based nutrition education intervention program on increasing behaviour to prevent iron deficiency anaemia in pregnant women. By (Ahmad et al, 2022), using a randomized cluster control study method, research conducted from October 2020 to March 2021 at the Darul Imarah Health Center in Aceh Besar District during the covid 19 pandemic showed that a structured education program for mothers during Pregnancy could improve the application of nutrition practices and health to prevent Anemia and KEK during Pregnancy.…”
Section: Introductionmentioning
confidence: 99%